The innovative development of the aphasia speech application for Thai adults with aphasia - Ruamsuk, Somjit; Kripanan, Nicha; Thanasriseabwong, Pornpat; Satityudhakarn, Pattarajarin; Ngamsuriyaroj, Sudsanguan (Journal of Associated Medical Sciences, 2025)
Background: The growing trend of internet usage among the Thai population, both in terms of user numbers and time spent online, has led to a growing demand for self-training applications. This trend presents opportunities to enhance access to healthcare services, especially in speech rehabilitation for aphasic patients. However, Thailand faces a shortage of speech-language pathologists (SLPs), making mobile applications a viable solution to expand access to treatment and improve patient outcomes. Objective: This study aimed to develop a digital tool for speech training in adult aphasic patients under the supervision of SLPs and a multidisciplinary team. It also sought to evaluate the tool’s effectiveness in improving speech outcomes for aphasic patients and assess user satisfaction among healthcare professionals, healthy participants, aphasic patients, and their caregivers. Materials and methods: This developmental research was conducted in four phases, starting with a literature review, developing the speech training application, expert validation of the application’s content, and tool implementation. The application was tested with 15 SLPs, six physicians, six nurses, six occupational therapists, six physical therapists, six healthy participants, 15 aphasic patients, and 15 caregivers. Based on the feedback from these diverse groups, the application was further refined to address suggestions and improve its usability. The application’s efficiency was measured through satisfaction surveys, while its effectiveness was evaluated using Thai adaptation of the Western Aphasia Battery test (WAB-Thai). Pre- and post-training scores were compared following 12 traditional speech therapy sessions with the Aphasia Speech application, each lasting 60 minutes over three months. Results: Satisfaction levels among healthcare professionals and healthy participants ranged from 4.0 to 4.2, whereas satisfaction levels among patients and caregivers were 3.9 to 4.6, indicating high satisfaction. The WAB-Thai scores showed statistically significant improvements in all areas, including fluency, comprehension, repetition, naming, reading, and the Aphasia Quotient (AQ) scores, with p<0.05. Conclusion: The developed application significantly enhanced the effectiveness of speech training, as evidenced by improved language and speech outcomes across all metrics. High satisfaction levels from users supported its implementation as a valuable tool for continuing speech therapy at home. Further refinements are necessary to optimize its usability, with plans for broader dissemination among healthcare providers to address the shortage of SLPs in underserved regions.